Trends in pediatric community-onset Staphylococcus aureus antibiotic susceptibilities over a five-year period in a multihospital health system - Erica C. Prochaska; Shaoming Xiao; Pranita D. Tamma; Anna Sick-Samuels; Christina Schumacher; Avinash Gadala; Karen C. Carroll; Aaron M. Milstone (Cambridge University Press, 2023)
The epidemiology of community-onset Staphylococcus aureus infections is evolving. We performed a multihospital, retrospective study of pediatric community-onset S. aureus susceptibilities between 2015 and 2020. Oxacillin and clindamycin susceptibility remained lower at 67% and 75%, respectively. Tetracycline and trimethoprim-sulfamethoxazole susceptibility remained high at >90%. Oxacillin susceptibility was highest in invasive infections.